2017
DOI: 10.17583/mcs.2017.2734
|View full text |Cite
|
Sign up to set email alerts
|

Masculinidades y emociones como construcciones socioculturales: una revisión (Masculinities and emotions as a sociocultural constructions: a review)

Abstract: It was conducted a literature review on the relationship between masculinities and emotions, both understood as social constructs that respond to particular contexts. The principal aim is to describe the scientific production considering some parameters proposed by bibliometric studies. A comprehensive search of articles based on the definition of specific keywords and criteria according to a wide variety of databases of full text documents. The results of the systematization review show a very slow growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Likewise, research has shown that dialogs among friends can create expectations about behavior and gender in relation to the aggressive behavior of men ( Kimmel, 1996 ; Giordano, 2003 ), so conversations within peer groups are likely to be shaped by the coercive discourse and might reproduce it. Yet the fact that the coercive discourse, and different kinds of masculinities and emotions ( Ramírez Rodriguez et al, 2017 ) have been socially constructed opens up the possibility for the subjects to enact their own agency and free choice, and modify the influence of such discourse ( Gómez, 2015 ; Puigvert, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, research has shown that dialogs among friends can create expectations about behavior and gender in relation to the aggressive behavior of men ( Kimmel, 1996 ; Giordano, 2003 ), so conversations within peer groups are likely to be shaped by the coercive discourse and might reproduce it. Yet the fact that the coercive discourse, and different kinds of masculinities and emotions ( Ramírez Rodriguez et al, 2017 ) have been socially constructed opens up the possibility for the subjects to enact their own agency and free choice, and modify the influence of such discourse ( Gómez, 2015 ; Puigvert, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Denying emotions is accompanied by the exaltation of reason as the proper vehicle to organize and make sense of the world. Some research has concluded that men are 150 Burbano-Valente -Masculinities in Transit  evasive regarding situations of stress or problems involving difficult emotional command, as they do not have the tools to face these problems because of a constant avoidance of their emotions (Berger, Shawab, Addis & Reigeluth, 2016, Balgane 2013, Ramírez Rodríguez, Gómez González, Gutiérrez de la Torre, & Sucilla Rodríguez 2017.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…En este trabajo en particular las emociones son comprendidas como estructuras primordiales para la construcción social, así como categorías de la cultura que permiten construir y comprender parte del universo de las relaciones sociales, en contextos geográficos e históricos determinados. Desde una perspectiva de género, en particular desde la masculinidad, se reconoce su vínculo estrecho entre emociones y construcción de la masculinidad [10][11][12][13][14][15][16] , emociones que socialmente se comprenden como exclusividad de lo femenino, aspecto que limita y condiciona el develamiento de las emociones en los varones, situación que establece desafíos para el acercamiento metodológico 2 , lo cual favorece pensar en el diseño y creación de estrategias cualitativas de recolección de la información 2,17 . En este contexto, la entrevista semiestructurada juega un papel importante y llevó a plantear varios interrogantes: ¿Cómo poder construir espacios con otro varón para hablar de las emociones?…”
Section: Introductionunclassified